A case of Angiolymphoid hyperplasia with eosinophilia in proximal ascending colon mimicking colon carcinoma (Bangladesh Journal of Medical Science, 2018)
Angiolymphoid hyperplasia with eosinophilia (ALHE) / Epithelioid hemangioma (EH) is a rare lesion commonly located in skin but arising in colon even rarer. It clinically follows a benign course of uncertain pathogenesis characterized histologically by plenty of proliferation of histiocytoid endothelial cells of blood vessels and infiltration by dense eosinophil, lymphocytes and plasma cells. The lesion may recur after excision but there is no report of metastasis. A case of sixty-four years male with severe pain in right iliac fossa with bloody stool had CT scan and noticed ulceration with bleeding sites on colonoscopy. Histopathological examination showed characteristic features of ALHE /EH in common location like skin. The lesion very often mimic as bleeding colonic carcinoma which necessitate colectomy. This is a rare case of ALHE /EH in proximal ascending colon.Bangladesh Journal of Medical Science Vol.17(1) 2018 p.158-160